Dysbiosis-associated gut bacterium Ruminococcus gnavus varies at the strain level in its ability to utilize key mucin component sialic acid - Olga M. Sokolovskaya; Jasmina Uzunovic; Yutian Peng; Mikiko Okumura; Lingjue Mike Wang; Yuhui Zhou; Zijuan Lai; Elizabeth Skippington; Man-Wah Tan (Microbiology Spectrum)
ABSTRACT Ruminococcus gnavus is a prevalent human gut commensal bacterium with known roles in intestinal mucus degradation, including by catabolism of the terminal mucin sugar sialic acid. While R. gnavus is not considered a pathogen, overabundance of this species is correlated with inflammatory bowel disease (IBD), and its sialic acid metabolism may play a role in the dysbiotic state. Interestingly, liberation of mucin-bound sialic acid by R. gnavus yields the distinct product of 2,7-anhydro-N-acetylneuraminic acid (2,7-anhydro-Neu5Ac), in contrast to other known mucin-degrading bacteria, which generate Neu5Ac. This prompted us to look for 2,7-anhydro-Neu5Ac metabolism proteins in the genomes of 77 R. gnavus clinical isolates. We found that 2,7-anhydro-Neu5Ac metabolism is sporadically distributed in this species with respect to phylogeny and strain origin. We measured sialic acid-dependent growth of 12 sequenced isolates, finding that the presence of 2,7-anhydro-Neu5Ac catabolism proteins was predictive of growth on this substrate. Our analysis also uncovered “partial” 2,7-anhydro-Neu5Ac catabolism pathways in two R. gnavus strains, leading to the discovery that these strains grow with Neu5Ac as a sole carbon source, a metabolic capability previously unreported in this species. These results reveal a notable diversity of sialic acid catabolism across the R. gnavus species, an essential consideration for further investigations into the importance of this metabolism in mucin degradation and in the roles of R. gnavus in IBD and other gut dysbioses.IMPORTANCERuminococcus gnavus is a common resident of the human gut, but often blooms in inflammatory bowel disease (IBD). It remains unclear whether R. gnavus plays any direct role in disease occurrence. This study investigates R. gnavus utilization of sialic acid, a crucial component of host mucins, the main constituents of the mucus that lines and protects the gut. We profile variations in sialic acid metabolic pathways and growth among 77 R. gnavus strains, isolated from healthy people and individuals with IBD, discovering further diversity in sialic acid utilization than was previously appreciated. This study emphasizes that the intricate interaction between bacteria and their environment must be examined at the strain level to understand the roles of particular species in health and disease.